The Impact of Perceived Value, Quality, and Loyalty on Purchase Decision in the Accessories Department: Study on Saudi Females - S. ALHuwaishel and Soad A. AL-Meshal, Najoud (British Journal of Marketing Studies, 2018)
The main purpose of this research is to study and investigate the impacts of perceived value, quality, and loyalty on the purchase decision. Furthermore, to understand the mediator impact of brand trust between the relation of consumers’ perceived value and the purchase decision. This research contains a study that is considered as an empirical study that follows a quantitative method and probability sampling technique. The questionnaire was conducted using internet-based survey where the sample includes random Saudi females living in Riyadh. The study shows that loyalty and quality have significant statistical impacts on the decision making. On the other hand, it shows that perceived value, has an influence on the brand trust but not on the purchase decision.